Thromboembolic complications in antiphospholipid syndrome and ankylosing spondylitis (two clinical cases) - K. S. Nurbaeva; F. A. Cheldieva; A. A. Shumilova; A. M. Lila; T. M. Reshetnyak (Современная ревматология)
We presented two clinical cases with clinical manifestations of antiphospholipid syndrome (APS) and ankylosing spondylitis (AS). The peculiarity of these cases is the onset of diseases in childhood, as well as the presence of not only extra-skeletal manifestations, but also complications or manifestations of other pathology. In the first case, it was thrombosis of the superficial veins of the lower limbs with the development of postthrombotic syndrome. In the second case, aortic valve defect, as a result of aortitis with a dilatation of the ascending aorta, which led to aortic valve replacement and its subsequent dysfunction because of thrombosis of the valve prosthesis. The frequency of detection of antiphospholipid antibodies (aPL), APS and thrombosis in AS is discussed. The role of tumor necrosis factor α (TNFα) inhibitors in the induction of aPL synthesis and the development of APS in patients with AS is considered either. Separately, we discussed the role of TNFα inhibitors, which are the main drugs in the treatment of ankylosing spondylitis, in the induction of aPL synthesis and the development of APS. Data on the occurrence of aPL, the reasons for the development of thrombosis in APS and the role of TNFα inhibitors remains incomplete. Perhaps the combination of APS and AS is an underestimated problem, and the information available in the literature does not reflect the real numbers. It is obvious that further research is needed to improve the treatment of patients with AS with thrombosis.